2021
DOI: 10.1002/ejp.1872
|View full text |Cite
|
Sign up to set email alerts
|

Pain catastrophizing mediates rapid benefits of accessing in‐person chiropractic care during the COVID‐19 lockdown

Abstract: Background In March 2020, the COVID‐19 pandemic forced the Spanish government to declare a state of emergency. A stringent lockdown was enforced, restricting access to healthcare services, including chiropractic. Reduced access to care provision in combination with psychological stress, social isolation and physical inactivity during the lockdown were shown to negatively influence pain conditions. However, data on strategies to mitigate the impact of the pandemic on these conditions are lacking. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 80 publications
(102 reference statements)
1
2
0
Order By: Relevance
“…Patients participating in the telehealth programme reported high levels of satisfaction (4.9/5 ± 0.4) 2 weeks after initiating the programme. These are comparable to the levels reported with in‐person care during the pandemic in Spain (Gevers‐Montoro et al, 2022) but largely exceed satisfaction amongst patients receiving other telehealth programmes (Carrillo‐de‐la‐Pena et al, 2021). Decreases in pain intensity with a large effect size ( η 2 p = 0.43) were also reported.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Patients participating in the telehealth programme reported high levels of satisfaction (4.9/5 ± 0.4) 2 weeks after initiating the programme. These are comparable to the levels reported with in‐person care during the pandemic in Spain (Gevers‐Montoro et al, 2022) but largely exceed satisfaction amongst patients receiving other telehealth programmes (Carrillo‐de‐la‐Pena et al, 2021). Decreases in pain intensity with a large effect size ( η 2 p = 0.43) were also reported.…”
Section: Discussionsupporting
confidence: 66%
“…For these patients, high scores in this subscale were associated with increased pain on day 14, whereas for those with low harm scores and the same motivation, pain decreased (see Figure 3a). This factor, which reflects the belief in the presence of a serious underlying pathology (Goubert et al, 2004), was also found to reduce the likelihood of benefitting from hands‐on care during the pandemic (Gevers‐Montoro et al, 2022). The present study expands on these findings by providing evidence that these beliefs, when combined with low motivation to actively engage in exercise whilst in home confinement, could lead to worsening of pain symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation